Optical coherence elastography: Strain imaging in tissue using optical coherence tomography - Kennedy, B.; Kennedy, K.; Ford, Christopher; McLaughlin, R.; Bush, M.; Sampson, D. (SPIE, 2012)
Optical coherence elastography (OCE) is a strain imaging technique that characterizes the elastic properties of tissues with microscopic resolution in three dimensions. In OCE, the displacement introduced to tissue by mechanical excitation is measured using optical coherence tomography. The local strain is calculated from the spatial derivative of displacement to generate strain images, known as elastograms. To validate elastograms, we compare them to a finite element analysis model of sample deformation. We also present preliminary OCE measurements performed on excised human breast tissue, and demonstrate discrimination of tissue types based on their elastic properties.